ANALYSIS OF MSME INCOME IN MEDAN CITY DURING THE COVID-19 PERIOD WITH MULTIPLE LINEAR REGRESSION METHODE - Sari, Nila; Dwi Tartila; Mahally, Jalaluddin; Khairul Furqan (Journal of Mathematics and Scientific Computing With Applications, 2021)
Micro, Small and Medium Enterprises (MSMEs) are an element of the phenomenon in today's economic world. With a capital that is not too large, you can start a business according to the desired goals. However, there are problems when operating whether MSMEs can survive and develop or can compete with large industries. Especially at this time around the world, being hit by the infectious disease covid-19 which has developed in 2020. The purpose of the study is to find out whether there is an influence from the development of covid-19 in the city of Medan on the income of MSMEs in the city of Medan. Data collection was carried out by interviewing several MSMEs around the city of Medan and taking the amount of data on Covid patients from the Medan City Government website, the Task Force for the Acceleration of Covid-19 Handling and the Medan City Health Office. To analyze the data, this research uses multiple linear regression analysis to see if there is an influence from Covid-19 on the development of Micro, Small, and Medium Enterprises in Medan City. The results of this study indicate that there is no significant effect of covid-19 between MSME income before the pandemic and the number of Covid-19 sufferers on MSME income when the pandemic increases.